New Internet domain .int - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
CTA now uses the top-level domain for inter-national organisations: .int .The CTA email address is now cta@cta.intThe Spore Web pages are now at: spore.cta.int (note: no need for www.)The old cta.nl address is still operating, but please change...